Removable uterine compression sutures for postpartum haemorrhage. (1st September 2014) - Zhang, ZW; Liu, CY; Yu, N; Guo, W
<x xml:space="preserve">Abstract</x> In 1997, B‐Lynch and colleagues introduced the B‐Lynch uterine compression suture for postpartum haemorrhage. Since then, various uterine compression sutures have been used and postpartum hysterectomy has been avoided in many women. However, some complications have emerged in years. In this article we discuss two types of uterine compression sutures in which stitches can be removed. The procedures have been successfully applied with no problems and no observed complications to date. This is a novel concept, with the potential to reduce morbidity related to compression sutures, but needs further evaluation.